Advanced laboratory stress-strain testing of geomaterials : outcome of TC 29 (Technical Committee No. 29) of ISSMGE (International Society for Soil Mechanics and Geotechnical Engineering) from 1994 to 2001 /: outcome of TC 29 (Technical Committee No. 29) of ISSMGE (International Society for Soil Mechanics and Geotechnical Engineering) from 1994 to 2001. (2018) - Unknown
No abstract available